Response of Rice Establishment Methods on Different Dates on Yield and Yield Attributing Characteristics of Rice in Mid-hills of Nepal - Chaulagain, Bhimsen; Karki, Tika Bahadur; Neupane, Reshama; Bhattarai, Rajendra Kumar; Gyawaly, Pankaj; Kaduwal, Sangita; Das, Soni Kumari (Agronomy Journal of Nepal, 2022)
An experiment was conducted in the summer season of 2019 and 2020 at the National Agronomy Research Centre to find out the response of various establishment methods and dates on the performance of rice. The experiment was carried out in 2 Factorial Randomized Complete Block (RCB) design with 3 replications in an area of 12 m2 and planting geometry of 25 cm between rows and 20 cm between plants.  The establishment methods were Sprouted Direct Seeded Rice (SDSR) broadcasting, puddled transplanting, and unpuddled transplanting at three dates viz. 10th June, 26th June, and 10th July. Twenty four hours water-soaked seeds were allowed to sprouting for 48 hours and broadcasted in a puddled plot. 22 days old seedlings were transplanted in a puddled and unpuddled plots.  Recommended doses of fertilizer @ 100:30:30 N:P2O5:K2O kg  ha-1 was used in the experiment. SDSR produced the highest yield of 4.2 Mt ha-1 compared to puddled transplanting method with 3.4 Mt ha-1. The highest grain yield was recorded on 10th June (5.9 Mt ha-1) followed by 26th June (4.0 Mt ha-1). Sprouted direct seeded rice permitted to mature early and produced the higher grain yield.